Analysis of Mathematical Reasoning Ability Based on Mathematics Anxiety In Junior High School Students - Agustin, Firnanda Shofiyah; Fauziyah, Nur; Khikmiyah, Fatimatul (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
Mathematical reasoning ability is one of the abilities that students must master. Influencing factors include math anxiety. This study analyzes and describes mathematical reasoning ability based on mathematics anxiety in junior high school students. The type of research conducted is descriptive qualitative research. This research was conducted at UPT SMP Negeri 17 Gresik class VII B with three students as research subjects for three categories of mathematical anxiety: high, medium, and low. Research data was obtained from mathematics anxiety questionnaires, reasoning ability tests, and interviews. Based on the results of the analysis, it was found that students with low levels of mathematical anxiety could fulfill all indicators of mathematical anxiety, and students with moderate levels of mathematical anxiety fulfilled three indicators of mathematical reasoning, namely making conjectures, manipulating mathematics, and determining patterns or properties of mathematical phenomena. Learners with high levels of mathematical anxiety only fulfill one indicator of mathematical anxiety, namely, making conjectures. From the results of the study, it can be concluded that the higher the students' mathematical anxiety, the lower their mathematical reasoning ability, so it is recommended that educators and students pay attention to mathematical anxiety in learning to improve their mathematical reasoning ability.